Opsoclonus-myoclonus syndrome with severe clinical course and beneficial outcome: A case report. Issue 14 (9th April 2021) - Koziorowska-Gawron, Ewa; Koszewicz, Magdalena; Bladowska, Joanna; Ejma, Maria; Budrewicz, Slawomir
Abstract: Rationale: Opsoclonus-myoclonus syndrome (OMS) is a rare immune-mediated movement disorder, mostly of paraneoplastic or idiopathic origin. The disease usually has an acute onset, serious course and leads rapidly to disability in adult patients. To the best of our knowledge, this is the fourth presented case of OMS with a severe course and complete reversibility of neurological symptoms in a pregnant woman. This report includes videos and a literature review. Patient concerns: A 30-year-old woman in the 12th week of pregnancy developed severe nausea and vomiting, after several days balance and gait disorders appeared. On admission to hospital, neurological examination revealed opsoclonus, dysarthria, myoclonic jerks with ataxia of the trunk and limbs with inability to sit, stand or walk. Diagnosis: Well-known causes of OMS were excluded. Although in our patient the idiopathic origin of the disorder was taken under consideration, diagnosis of opsoclonus-myoclonus related to the pregnancy was highly likely. Interventions: After administration of steroids and benzodiazepines the patient improved. Outcomes: In the 6th month of pregnancy, after termination of immunotherapy, she recovered completely and was able to sit, stand and walk independently. In the 39th week of pregnancy, she delivered a healthy child. Lessons: We confirm that understanding of clinical symptoms and rare causes of OMS contributes to early diagnosis and therapy, which ensures an optimal outcome. One probable cause of OMS could be a physiological change to immune system regulation during pregnancy. The relationship between OMS and pregnancy remains uncertain and needs further investigation. Abstract : Supplemental Digital Content is available in the text